Conflict side of creativity: Role of supervisory support and team affective tone in facilitating creative idea validation - Adeel, Ahmad; Kee, Daisy Mui Hung; Qasim Daghriri, Yahya (Frontiers in Public Health, 2022)
Purpose- We seek to understand whether relationship conflicts of co-workers affect the validation of creative ideas or not. Furthermore, what boundary conditions may help prevent potential drawbacks of relationship conflicts with co-workers to validate their creative ideas. Design/methodology/approach- The proposed model was tested by using multisource data collected across two points in time from final year nursing students and medical dispensers of five nursing colleges of south-punjab, Pakistan. The model was analyzed with Mplus for random coefficient models for direct effects, mediated moderation, and UCINET for central tendency of creative idea validation. Findings- It was found that relationship conflicts with co-workers were negatively related to their validation of creative ideas. However, supervisory support and team affective tone independently attenuate the negative effects of relationship conflicts with co-workers and the validation of creative ideas. Positive affective tone emerged as a positive predictor of creative idea validation. Additionally, positive affective tone as affected by supervisory support attenuated the negative relationship between relationship conflicts with co-workers and their validation of creative ideas. Finally, the relationship between relationship conflicts with co-workers and their validation of creative ideas is more positive when both supervisory support and positive affective tone are high, however, low otherwise. Practical implications- This study will help policymakers understand what might be hindering the transfer of creative ideas to influence others (Leaders, Managers, etc.) and what they need to do to enhance the creative pool of their organizations. Although developing an environment that fosters creativity is important for the organizations, developing strategies to manage relationship conflicts related to supervisory support and positive affective tone will help transfer creative ideas to higher offices even when there are dysfunctional conflicts. Originality/value- This research shifts the conventional focus of understanding creativity from the generating side by explaining challenges that creative individuals face in promoting creative ideas with more criticism and offense by coworkers than support. Also, the interplay between the relationship conflicts with co-workers and team affective tone affected by supervisory support for validation of creative ideas enhanced our understanding of the boundary conditions of relationship conflict and creative idea validation.